Differentiated thyroid cancer and adverse pregnancy outcomes: a propensity score-matched retrospective cohort study - Li, Xin; Mei, Fang; Xiao, Wu-Cai; Zhang, Fan; Zhang, Shanghang; Fu, Peng; Chen, Jing; Shan, Rui; Sun, Bang-Kai; Song, Shi-Bing; Yuan, Chunhui; Liu, Zheng (Frontiers in Pediatrics, 2024)
Background: Differentiated thyroid cancer (DTC) has been increasingly common in women of reproductive age. However, the evidence remainsed mixed regarding the association of DTC with adverse pregnancy outcomes in pregnant women previously diagnosed with DTC.We conducted a retrospective cohort study in the Peking University Third Hospital in Beijing, China between January 2012 and December 2022. We included singleton-pregnancy women with a pre-pregnancy DTC managed by surgical treatment (after-surgery DTC) or active surveillance (under-surveillance DTC). To reduce the confounding effects, we adopted a propensity score to match the after-surgery (n = 204) and under-surveillance DTC (n = 37) groups with the non-DTC group (n = 816 and 148; matched with the former and latter DTC group), respectively, on age, parity, gravidity, pre-pregnancy weight, height, and Hashimoto's thyroiditis. We used conditional logistics regressions, separately for the after-surgery and under-surveillance DTC groups, to estimate the adjusted associations of DTC with both the composite of adverse pregnancy outcomes and the specific mother-, neonate-, and placentarelated pregnancy outcomes.After the propensity-score matching, the DTC and non-DTC groups were comparable in the matched, potentialmeasured confounders. In the after-surgery DTC group (n = 204), the risk of the composite or specific adverse pregnancy outcomes was not significantly different from that of the matched, non-DTC groups (n = 816; P > 0.05), and the results showed no evidence of difference across different maternal thyroid dysfunctions, gestational thyrotropin levels, and other pre-specified subgroup variables. We observed broadly similar results in the under-surveillance DTC group (n = 37), except that the risk of preterm birth, preeclampsia, and deliverhaving thea low-birth-weight birthsaby was higher than that of the matched, non-DTC group [n = 148; OR (95% CI): 4.79 (1.31, 17.59); 4.00 (1.16, 13.82); 6.67 (1.59, 27.90)].Conclusions: DTC was not associated with adverse pregnancy outcomes in pregnant women previously treated for DTC. However, more evidence is urgently needed for pregnant women with under-surveillance DTC, which finding will be clinically significant in individualizing prenatal care.